Understanding the water absorption from MHEC modified glue mortar into porous tile: Influence of pre-drying. (30th August 2019) - Faiyas, A.P.A.; Erich, S.J.F.; Huinink, H.P.; Adan, O.C.G.
Highlights: Water from glue mortar transports to tile, during drying the water returns to the hydrating mortar. A high viscosity of MHEC solution decreases the uptake of water in the tile and substrate. Dry air induces a dry region at the mortar surface that inhibits wetting by tile. Stagnant air delays formation of a dry region at the mortar surface, ensuring sufficient wetting by tile. Abstract: This article presents an experimental investigation on the influence of Methylhydroxyethylcellulose (MHEC) modified mortar on water absorption into tile and base substrate using Nuclear Magnetic Resonance (NMR) imaging. Addition of MHEC shifts the absorption behavior from homogeneous to inhomogeneous as a result of increased viscosity of pore solution. The observed reverse flow from tile to mortar is a result of decrease in capillary pressure in mortar as a consequence of decrease in pore size due to hydration. Pre-drying of 1.3 wt% MHEC mortar with dry air shows little wetting by tile due to MHEC transport and formation of dry region at the mortar surface. On the contrary, pre-drying of 1.3 wt% MHEC mortar at 40% RH slows down MHEC transport and delays the formation of dry region at the mortar surface enabling higher wetting by tile.